Kulturowe uwarunkowania zmian w systemie zarządzania w montowni samochodów General Motors we Fremont (Kalifornia) - Pilcer, Helena (Cultural determinants of changes in management system of general motors manufacturing plant located in fremont, california, 2005)
Organizational culture is underlying principle of Japanese enterprises management system. The paper presents the process of forming an organizational culture in Toyota Motor Manufacturing and an important role of this culture in an efficient performance of management system of General Motors manufacturing plant located in Fremont, California.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 666-672